2022
DOI: 10.3390/socsci11080365
|View full text |Cite
|
Sign up to set email alerts
|

The Uses of Coffee in Highly Demanding Work Contexts: Managing Rhythms, Sleep, and Performance

Abstract: This paper presents a sociological approach to coffee consumption as a performance management strategy in work contexts, particularly in professions with intense work rhythms and highly responsive demands. Focusing on the daily work of three professional groups (nurses, police officers, and journalists), we analyze the social expression of coffee and how it is mobilized to deal with sleep problems, fatigue, concentration, or stress. For this purpose, three intertwined dimensions are explored: (1) the nature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…Thus, the results showed that the two main reasons are the taste of caffeinated drinks and their physiological effect (i.e., to stay awake). These reasons for consuming caffeinated drinks are in line with the findings of other studies [ 11 , 14 , 22 ]. These results were similar for both sexes; however, other reasons were considered.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, the results showed that the two main reasons are the taste of caffeinated drinks and their physiological effect (i.e., to stay awake). These reasons for consuming caffeinated drinks are in line with the findings of other studies [ 11 , 14 , 22 ]. These results were similar for both sexes; however, other reasons were considered.…”
Section: Discussionsupporting
confidence: 91%
“…Concerning caffeine consumption, coffee remains the primary source of caffeine intake, which corroborates the results in most European countries and the United States of America [ 7 , 19 , 21 , 22 ]. Approximately two billion coffee “express” are estimated to be consumed every day in the world [ 23 ].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations